Tumor-suppressive function of methiothepin in human placental choriocarcinoma cells. Issue 6 (December 2020) - Lee, Jin-Young; Lim, Whasun; Song, Gwonhwa
Abstract : Placental choriocarcinoma is a malignant trophoblastic tumor associated with placentation. During placentation, complicated molecular networks are mediated by endocrine and paracrine signals. Serotonin neurotransmitters have been identified in the transmembrane region of human placental choriocarcinoma (HPC) cells as tumor promoters; therefore, their antagonists have anti-cancer properties. Although methiothepin, a serotonin receptor antagonist and FDA-approved psychotropic agent, has shown multi-pharmacological functions in various disease models, its anti-tumorigenic activity and mechanisms underlying its action against HPC are unknown. Therefore, we identified the anti-cancer effects of methiothepin in JEG3 and JAR HPC cells. Methiothepin attenuated mitochondrial function and induced endoplasmic reticular stress, reducing oxidative phosphorylation and causing metabolic shifting in HPC cells. Furthermore, methiothepin showed synergistic pharmacological effects with paclitaxel in HPC cells. Our results highlight the robust tumor-suppressive function of methiothepin in HPC. Our findings provide new insights into the repositioning of methiothepin from a psychotropic agent to novel anti-cancer agents, especially against HPC.